2023
DOI: 10.7759/cureus.46006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation in the Modern Era: Optimizing Recovery and Reducing Recurrence

Amna Zaree,
Shah Dev,
Iqra Yaseen Khan
et al.

Abstract: Cardiovascular diseases (CVDs) continue to be a prominent issue in global health, emphasizing the necessity for efficient cardiac rehabilitation programs. This narrative review provides a detailed analysis of the current state of cardiac rehabilitation, focusing on maximizing recovery and minimizing the likelihood of recurrence. This paper examines the historical progression of cardiac rehabilitation, explores the epidemiological background of cardiovascular disease (CVD), and provides an overview of the many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
(224 reference statements)
0
12
0
3
Order By: Relevance
“…This aligns with previous research that suggests behavioral interventions, such as smoking cessation programs and dietary counseling, can lead to better cardiovascular outcomes. 5 The role of healthcare professionals like cardiac nurses and nutritionists in behavior modi cation was crucial. Studies have shown their impact on lifestyle changes after a heart attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with previous research that suggests behavioral interventions, such as smoking cessation programs and dietary counseling, can lead to better cardiovascular outcomes. 5 The role of healthcare professionals like cardiac nurses and nutritionists in behavior modi cation was crucial. Studies have shown their impact on lifestyle changes after a heart attack.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, behavioral therapies tailored to individual patient requirements and preferences are more likely to encourage long-term adherence, encourage favorable health behaviors, and lower the risk of recurrent cardiac episodes. 5 Understanding the behavioral changes after a heart attack is crucial for designing effective interventions and support systems. The insights gained from participants, including their willingness to modify lifestyle habits, awareness of dietary impacts, and their challenges, form the basis for developing targeted strategies.…”
mentioning
confidence: 99%
“…The historical account of the development of cancer treatments and their effects on the cardiovascular system spans several decades, illustrating the complex relationship between improvements in cancer therapy and the growing understanding of cardiovascular problems [ 1 ]. This chronicle of events in oncology and cardiology highlights important milestones, revealing the progressive acknowledgment of cardiovascular complications linked to early cancer therapies.…”
Section: Reviewmentioning
confidence: 99%
“…It combines knowledge from both cardiology and oncology to provide a crucial answer to this issue. With the progress of medical technology, cancer patients are living longer [ 1 ]. Consequently, there is now a focus on understanding and managing the intricate relationship between cancer and cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and hostility are also associated not only with increased cardiac morbidity in healthy people but also poor prognosis in patients affected by chronic heart diseases [13]. Multidisciplinary cardiac rehabilitation (CR) is a multidisciplinary systematic approach designed to apply secondary prevention therapies of known benefit, inclusive of medical evaluation, prescriptive exercise, cardiac risk factor modification, education, counselling, and behavioral interventions [14,15]. CR could be a proper time to identify emotional disorders or psychological distress and define a specific psychological profile to help patients to cope with stressful events in order to improve their outcomes [16].…”
Section: Introductionmentioning
confidence: 99%